Providing community-based health practitioners with timely and accurate discharge medicines information - Gilbert Alice V; Patel Bhavini; Morrow Melanie; Williams Desmond; Roberts Michael S; Gilbert Andrew L (BMC, 2012)
Abstract Background Accurate and timely medication information at the point of discharge is essential for continuity of care. There are scarce data on the clinical significance if poor quality medicines information is passed to the next episode of care. This study aimed to compare the number and clinical significance of medication errors and omission in discharge medicines information, and the timeliness of delivery of this information to community-based health practitioners, between the existing Hospital Discharge Summary (HDS) and a pharmacist prepared Medicines Information Transfer Fax (MITF). Method The study used a sample of 80 hospital patients who were at high risk of medication misadventure, and who had a MITF completed in the study period June - October 2009 at a tertiary referral hospital. The medicines information in participating patients' MITFs was validated against their Discharge Prescriptions (DP). Medicines information in each patient's HDS was then compared with their validated MITF. An expert clinical panel reviewed identified medication errors and omissions to determine their clinical significance. The time between patient discharge and the dispatching of the MITF and the HDS to each patient's community-based practitioners was calculated from hospital records. Results DPs for 77 of the 80 patients were available for comparison with their MITFs. Medicines information in 71 (92%) of the MITFs matched that of the DP. Comparison of the HDS against the MITF revealed that no HDS was prepared for 16 (21%) patients. Of the remaining 61 patients; 33 (54%), had required medications omitted and 38 (62%) had medication errors in their HDS. The Clinical Panel rated the significance of errors or omissions for 70 patients (16 with no HDS prepared and 54 who's HDS was inconsistent with the validated MITF). In 17 patients the error or omission was rated as insignificant to minor; 23 minor to moderate; 24 moderate to major and 6 major to catastrophic. 28 (35%) patients had their HDS dispatched to their community-based practitioners within 48 hours post discharge compared to 80 (100%) of MITFs. Conclusion The MITF is an effective approach for the timely delivery of accurate discharge medicines information to community-based practitioners responsible for the patient's ongoing care.